Sleep and circadian rhythm disruption in psychiatric and neurodegenerative disease. - Wulff, K; Gatti, S; Wettstein, J; Foster, R (2010)
Sleep and circadian rhythm disruption are frequently observed in patients with psychiatric disorders and neurodegenerative disease. The abnormal sleep that is experienced by these patients is largely assumed to be the product of medication or some other influence that is not well defined. However, normal brain function and the generation of sleep are linked by common neurotransmitter systems and regulatory pathways. Disruption of sleep alters sleep-wake timing, destabilizes physiology and promotes a range of pathologies (from cognitive to metabolic defects) that are rarely considered to be associated with abnormal sleep. We propose that brain disorders and abnormal sleep have a common mechanistic origin and that many co-morbid pathologies that are found in brain disease arise from a destabilization of sleep mechanisms. The stabilization of sleep may be a means by which to reduce the symptoms of--and permit early intervention of--psychiatric and neurodegenerative disease.